2021
DOI: 10.1186/s12889-021-10956-w
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation, physical inactivity and inadequate diet among European middle-aged and older adults

Abstract: Background Social isolation is a growing public health concern for older adults, as it has been associated with poor health and premature mortality. On the other hand, physical inactivity and an inadequate diet are important health risk behaviours associated with physical and mental health problems. Considering that there is no research examining the possible relationship between social isolation and the above mentioned health risk behaviours of European middle-aged and older adults, this cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Reduced social interaction has been observed in rodents fed a Western-style diet [ 62 , 63 ] and in the offspring of rodents [ 64 , 65 , 66 ] and female Japanese macaques [ 40 ] that consumed a Western-style diet during gestation. In human observational studies of self-reported diet and social characteristics, social isolation is associated with Western diet consumption [ 41 , 67 ], whereas adherence to a Mediterranean diet is correlated with decreased isolation [ 68 ]. The findings reported here are novel in their observations, including the rapidity with which behavior changed in response to dietary changes; the longitudinal persistence of behavior changes over two years (a timespan roughly equivalent to seven human years); the observation that the Mediterranean diet drove most of the differences in behavior and the randomized trial design that allows for causal inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced social interaction has been observed in rodents fed a Western-style diet [ 62 , 63 ] and in the offspring of rodents [ 64 , 65 , 66 ] and female Japanese macaques [ 40 ] that consumed a Western-style diet during gestation. In human observational studies of self-reported diet and social characteristics, social isolation is associated with Western diet consumption [ 41 , 67 ], whereas adherence to a Mediterranean diet is correlated with decreased isolation [ 68 ]. The findings reported here are novel in their observations, including the rapidity with which behavior changed in response to dietary changes; the longitudinal persistence of behavior changes over two years (a timespan roughly equivalent to seven human years); the observation that the Mediterranean diet drove most of the differences in behavior and the randomized trial design that allows for causal inferences.…”
Section: Discussionmentioning
confidence: 99%
“…Through a Confirmatory Factor Analysis (CFA), a latent continuous physical health measure was constructed (Delerue Matos et al., 2021 ; Di Gessa et al., 2016 ; Ploubidis & Grundy, 2011 ). This physical health measure includes one objective health indicator, plus six subjective ones.…”
Section: Methodsmentioning
confidence: 99%
“…This physical health measure includes one objective health indicator, plus six subjective ones. Maximum grip strength using one or both hands is the objective health indicator used, while self‐perceived health (poor (1), fair (2), good (3), very good (4) or excellent (5)); having a long‐term illness; reporting limited activities because of health (1 ‐ severely limited, 2 ‐ limited, but not severely; and 3 ‐ not limited); having had a heart attack; having had a stroke; and having had chronic lung disease are the subjective ones (Delerue Matos et al., 2021 ). Our F‐score varies from −1.89 to 1.32, meaning that higher scores indicate better physical health.…”
Section: Methodsmentioning
confidence: 99%
“…Another public health concern impacting mental well-being is isolation (Delerue Matos et al, 2021). Like Yardley and Rusu’s (2018) findings, engaging with Staging Time assisted in encouraging prisoners and incarcerated audience members to join other activities.…”
Section: Benefits To Health and Well-beingmentioning
confidence: 99%